2018
DOI: 10.1002/rcr2.383
|View full text |Cite
|
Sign up to set email alerts
|

Gastric perforation related to concurrent use of nintedanib and ramucirumab

Abstract: The prevalence of lung cancer in idiopathic pulmonary fibrosis (IPF) patients ranges from 9.8 to 38%. Nintedanib, a small molecule receptor tyrosine kinase inhibitor (TKI) of platelet‐derived growth factor receptor (PDGFR), fibroblast growth factor receptor (FGFR), and vascular endothelial growth factor receptor (VEGFR), has been approved for IPF after phase III INPULSIS trials in 2014. Ramucirumab, a monoclonal antibody for VEGFR‐2, combined with docetaxcel, has been approved for advanced non‐small cell lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Likewise, several case studies in humans have reported anastomotic leak in the bowel following initiation of TKIs. 13-18 We now infer a similar contributory mechanism of TKIs to the development of gastropharyngeal leak in our patient. While the exact mechanism of action of this side effect is unclear, we look to the evidence of other animal studies as a possible starting point for an answer.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Likewise, several case studies in humans have reported anastomotic leak in the bowel following initiation of TKIs. 13-18 We now infer a similar contributory mechanism of TKIs to the development of gastropharyngeal leak in our patient. While the exact mechanism of action of this side effect is unclear, we look to the evidence of other animal studies as a possible starting point for an answer.…”
Section: Discussionsupporting
confidence: 62%
“…More recently, gastric perforations have also been described with use of the newer TKIs Nintedanib, Ramucirumab, and Regorafenib. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…We found 29 completed studies evaluating FGFR -targeting drugs in 11 of 14 cancer types analyzed in the off-label estimations (Table 2). 12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38 There were 8 (27.6%) case reports, 1 (3.4%) case series, 9 (31.0%) phase 1 studies, 2 (6.9%) phase 1/2 studies, and 9 (31.0%) phase 2 studies. While 2 phase 2 trials (22.2%) were randomized, the rest were noncomparator trials.…”
Section: Resultsmentioning
confidence: 99%